Protective Factors for Marijuana Use and Suicidal Behavior Among Black LGBQ U.S. High School Students - DeKeitra Griffin; Shawndaya S. Thrasher; Keith J. Watts; Philip Baiden; Elaine M. Maccio; Miya Tate (Social Sciences)
This study aimed to investigate the association between protective factors, marijuana use, and suicidal behavior among Black LGBQ U.S. adolescents. Methods: A subsample of 991 Black LGBQ adolescents was derived from the 2019 Combined High School YRBSS dataset. Suicidal behavior was measured as suicidal planning and/or previous suicide attempts. Marijuana usage gauged lifetime consumption. The protective factors included sports team participation, physical activity, eating breakfast, hours of sleep, and academic performance. Age and sex were entered as covariates. Multiple imputation by chained equations (MICE) was used to address missing data, and pooled binary logistic regression analyses were conducted. Results: Academic performance and hours of sleep were significantly associated with lower odds of suicidal behavior and lifetime marijuana use. Sports team participation was associated with higher odds of lifetime marijuana use. Being female was linked to higher odds of marijuana use, while older age was associated with lower odds. Discussion: For Black LGBQ youth, academic performance and sufficient sleep may function as protective factors. Participating in sports was associated with greater odds of risk behaviors, highlighting the need to assess the experiences of Black LGBQ youth in sports. Implications and Contributions: Our findings inform school programming, policy, and practice by identifying academic support and sleep health as intervention areas.